The possible therapeutic role of curcumin and quercetin in the early-stage of COVID-19—Results from a pragmatic randomized clinical trial - Ujjan, Ikram Din; Khan, Saeed; Nigar, Roohi; Ahmed, Hammad; Ahmad, Sagheer; Khan, Amjad (Frontiers in Nutrition, 2023)
Background Curcumin (CUR) and quercetin (QUE), two natural polyphenols, possess diverse biological activities including broad-spectrum antiviral, antioxidant, and immunomodulatory effects. Both CUR and QUE have shown inhibition of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in in vitro assays. Objective In the present study we aimed to assess the possible treatment benefits of a combined curcumin and quercetin (CUR-QUE) oral supplement, alongside standard of care (SOC), in the early-stage COVID-19 infection. Methods This was an exploratory, pragmatic, open-label, randomized controlled clinical trial, conducted at the Department of Pathology, Liaquat University of Medical and Health Sciences, Jamshoro, PK. The study compared the treatment effect of an oral CUR-QUE supplement plus SOC vs. SOC alone, in the early-stage/mild to moderately symptomatic COVID-19 outpatients. Patients were randomized in a 1:1 ratio to CUR-QUE (n = 25) and control (n = 25) treatment groups. The CUR-QUE supplementation consisted of a daily intake of 168 mg curcumin and 260 mg quercetin, as two soft capsules, to be taken twice a day at home for 14 days. Results After one-week of treatment, most of the patients in the CUR-QUE group showed an expedited clearance of the viral infection i.e., 18 (72.0%) vs. 6 (24.0%) patients in the control group tested negative for SARS-CoV-2 in the nasal-oropharyngeal swab reverse transcription-polymerase chain reaction (RT-PCR) analysis (p = 0.0002). In addition, COVID-19-associated acute symptoms were also speedily resolved in the CUR-QUE treated patients, i.e., 10 (40.0%) vs. 4 (16.0%) patients in the control group (p = 0.061). The CUR-QUE supplementation therapy was well-tolerated by all 25 patients and no treatment-emergent effects or serious adverse events were reported. Conclusion The results revealed in this exploratory study suggest a possible therapeutic role of curcumin and quercetin in the early-stage of COVID-19. It is proposed that the two agents possibly acting in synergy, interfere the SARS-CoV-2 replication, and thus help a speedy recovery in the early-stage of COVID-19. Further research is highly encouraged. Clinical trial registration Clinicaltrials.gov, Identifier NCT04603690.